Mechanism of magnetization reduction in iron oxide nanoparticles. Issue 14 (7th April 2021) - Köhler, Tobias; Feoktystov, Artem; Petracic, Oleg; Kentzinger, Emmanuel; Bhatnagar-Schöffmann, Tanvi; Feygenson, Mikhail; Nandakumaran, Nileena; Landers, Joachim; Wende, Heiko; Cervellino, Antonio; Rücker, Ulrich; Kovács, András; et al.
Abstract : Antiphase boundaries in iron oxide nanoparticles with oleic acid coating were found to be a major contributor to the observed reduction in saturation magnetization. Abstract : Iron oxide nanoparticles are presently considered as main work horses for various applications including targeted drug delivery and magnetic hyperthermia. Several questions remain unsolved regarding the effect of size onto their overall magnetic behavior. One aspect is the reduction of magnetization compared to bulk samples. A detailed understanding of the underlying mechanisms of this reduction could improve the particle performance in applications. Here we use a number of complementary experimental techniques including neutron scattering and synchrotron X-ray diffraction to arrive at a consistent conclusion. We confirm the observation from previous studies of a reduced saturation magnetization and argue that this reduction is mainly associated with the presence of antiphase boundaries, which are observed directly using high-resolution transmission electron microscopy and indirectly via an anisotropic peak broadening in X-ray diffraction patterns. Additionally small-angle neutron scattering with polarized neutrons revealed a small non-magnetic surface layer, that is, however, not sufficient to explain the observed loss in magnetization alone.